High-grade broad ligament cancer of müllerian origin: immunohistochemical analysis of a case and review of the literature. Issue 3 (1st May 2007) - Handa, Y.; Kato, H.; Kaneuchi, M.; Saitoh, Y.; Yamashita, K.
Abstract : Malignant neoplasms arising in the broad ligament are quite unusual. Although tens of broad ligament cancers of low potential malignancy have been documented, there have been only two reports of high-grade cases. Furthermore, it remains controversial whether broad ligament tumors are mesonephric (wolffian) or paramesonephric (müllerian) in origin. This case study reports a 49-year-old nulliparous woman who, during her follow-up for breast cancer, demonstrated a 39- × 32-mm solid and poorly differentiated adenocarcinoma within the broad ligament of the right adnexa. Because of its rarity and poor differentiation, immunohistochemical analysis was performed to identify the primary malignancy and determine its origin. Positive expression of WT1, CA125, and ER and negative expression of GCDFP-15, HER-2, and PgR in broad ligament cancer, in conjunction with positive expression of GCDFP-15 and ER and negative expression of WT1, HER-2 and PgR in the previous breast cancer, suggested broad ligament cancer to be a gynecological primary malignancy with serous characteristics rather than a metastasis from the previous breast cancer. In addition, EMA-positive and CK7-negative expression indicated a müllerian origin. Broad ligament cancers of müllerian origin occur predominantly in women of reproductive age, most of whom are infertile or nulliparous. This feature, together with the positive expression of ER in this case, may raise the possible hormonal influence on the etiology of broad ligament cancer of müllerian origin.